Please, Download the Guidelines for Authors Here, and Read Carefully Before Submitting - Nko'o Amvene, Samuel (HEALTH RESEARCH IN AFRICA, 2024)
I. JOURNAL SCOPE Health Research in Africa (HRA) is a peer reviewed scientific that is affiliated to Health Sciences and Disease. HRA covers all aspects of medicine, pharmacy, biomedical and health sciences, including public health and societal issues. It is an “online first” publication, which means that all the publications articles appear on the website before being included in the print journal. The papers are published in full on the website, with open access. Our mission is to inform and educate all the health professionals and to promote constructive debate on health issues that matter in the management not only of diseases but of health as a whole. Acceptance of manuscripts is based on the originality, the quality of the work and validity of the evidence, the clarity of presentation, and the relevance to our readership. Publications are expected to be concise, well organized and clearly written. Authors submit a manuscript with the understanding that the manuscript (or its essential substance) has not been published other than as an abstract in any language or format and is not currently submitted elsewhere for print or electronic publication. Manuscripts must be submitted by one of the authors of the manuscript. The submitting author takes responsibility for the article during submission and peer review. The HRA editorial team is based in Yaounde (Cameroon). II. MANUSCRIPT SUBMISSIONS The preferred way for submission is the online submission. Please, refer to the Health Research in Africa home page: http://hsd-fmsb.org/index.php/HRA/. Otherwise, manuscripts can be addressed to nkooamvenes@gmail.com. Inquiries about manuscript status and preparation, as well as letters to the editor, should be directed to / Nko’o Amvene Samuel Editor-in-Chief. Health Research in Africa Afrimvoe Medical Services PO Box 17583, Yaoundé Cameroon. Email: nkoo_as@yahoo.com Fast track Please, send a copy to the Editor in Chief and ask fast track. Special article processing charges may be required.